Bearing Capacity of Hollow GFRP Pipe-Concrete-High Strength Steel Tube Composite Long Columns Under Eccentrical Compression Load - Ji, Jing; Zeng, Wen; Wang, Ruili; Ren, Hongguo; Zhang, Lei; Liu, Yuchen; Jiang, Liangqin; He, Lingjie; Lin, Yubo; Yu, Chenyu (Frontiers in Materials, 2021)
In order to investigate the bearing capacity of the Hollow GFRP pipe-concrete-steel tube composite long columns subjected to eccentrical compression load, 33 Hollow GFRP pipe-concrete-steel tube composite long columns were designed. The slenderness ratio(λ), compressive strength of concrete cube (fcu), eccentricity (e), thickness of GFRP pipe (t1) and thickness of steel tube (t2) were considered as main parameters. Based on stress hardening elastoplastic constitutive model for the steel, elastic constitutive model for GFRP, and confined constitutive model for concrete, numerical simulation analysis of the Hollow GFRP pipe-concrete-high strength steel tube composite long columns was carried out by using finite element software ABAQUS. The rationality of the constitutive model and modeling method was verified by comparing the load-displacement curves between experiments and simulations. Based on this, the extended parameter analysis of the hollow GFRP pipe-concrete-high strength steel tube composite long columns were conducted, and the influence regularity of different parameters on the mechanical behavior of the hollow GFRP pipe-concrete-high strength steel tube composite long columns was investigated. The results show that with the increasing of t1、t2 and fcu, the ultimate eccentrical compression bearing capacity of the specimen increases. With the increasing of e, the ultimate displacement of the specimens increases, while the ultimate eccentrical compression bearing capacity decreases. The eccentricity has a significant influence on the ultimate eccentrical compression bearing capacity of the specimens. With the increasing of λ, the ultimate eccentrical compression bearing capacity of the specimens gradually decreases. The load-displacement curves of the composite long columns consist of four stages of elastic, elastoplastic, plastic and load-holding. The failure process of the specimens presents certain characteristics, which belongs to ductile failure. At last, based on the empirical coefficient method, the calculation formula of the ultimate eccentrical compression bearing capacity of the composite columns is obtained by statistical regression.